Resource allocation for secure OFDMA decode-and-forward relay networks - Ng, Derrick Wing Kwan; Schober, Robert (12th Canadian Workshop on Information Theory, CWIT 2011, 2011)
In this paper, we formulate an optimization problem for resource allocation and scheduling in orthogonal frequency division multiple access (OFDMA) half-duplex decode-and-forward (DF) relay assisted networks. Our problem formulation takes into account artificial noise generation to combat a multiple antenna eavesdropper. The secrecy data rate, power, and sub-carrier allocation policies are optimized to maximize the average secrecy outage capacity (bit/s/Hz securely delivered to the users via relays). The optimization problem is solved by dual decomposition which results in an efficient iterative algorithm. Simulation results illustrate that the proposed iterative algorithm converges in a small number of iterations and guarantees a non-zero secrecy date rate for a given target secrecy outage probability. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03